Health Risk Assessment of Heavy Metals in Soils before Rice Sowing and at Harvesting in Southern Jiangsu Province, China - Chenghui Han; Weifang Xie; Chen Chen; Ting Cheng (Journal of Chemistry)
Rice, one of the most important staple crops in China, is easily contaminated by heavy metal pollution from industrial development. In this work, we systematically investigated the heavy metal (Cr, Cd, Pb, Zn, and Cu) and metalloid (Hg and As) concentrations in paddy soils and different rice tissues in southern Jiangsu Province, China. The potential ecological hazard index method and in vitro simulation test were used to evaluate the influence of heavy metals on local resident health. The results showed that, before rice sowing and at the harvesting period, the order of Eri values was EriCd>EriHg>EriAs>EriPb>EriCu>EriCr>EriZn. The low-risk index values (91.63 and 30.29) for the heavy metals indicated the low risk at the two stages in the study area based on the potential ecological hazard index. As determined with Tessier’s five-stage sequential extraction procedure, the proportions of the chemical speciation of the heavy metals were as follows: residual > organic matter-bound > iron-manganese oxide-bound > carbonate-bound > exchangeable. The order of the values of the accumulation and transfer factors was Cd (3.16) > Cu (0.42) > Zn (0.28) > Pb (0.25) > As (0.07) > Cr (0.04) > Cr (0.03) and root > stem > leaves, respectively. In vitro simulation tests showed that, in both adults and children, the daily amount of Pb and Cd intake through the soil-oral cavity route in the study area did not exceed the daily tolerance for Pb and Cd proposed by the WHO. In summary, although there is no obvious danger to local adults and children, it is necessary to be aware of the possibility of rice contamination from Cd in the soil.